Georges Sorel's study on Vico - Sorel, Georges, 1847-1922 (Radboud studies in humanities, 2020)
"Georges Sorel's Study on Vico is a revelatory document of the depths and stakes of French social thought at the end of the 19th century. What brought Sorel to the 18th century Neapolitan theorist of history? Acute awareness of the limitations of Marxist thought in his day, a profound concern with the material underpinnings of language, law, and culture, and the imperative to understand the possibilities of revolutionary change. We find here a different Sorel, one who speaks in surprising ways to the 21st century. The translation is accompanied by an introduction and by a set of notes which situate the text both in Sorel's overall intellectual trajectory and in the fin de siècle debates from which it emerged"--